LHEP 2018
DOI: 10.31526/lhep.1.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Newtonian Cosmological Models in Scalar-Tensor Theories of Gravity

Abstract: In this contribution, classes of shear-free cosmological dust models with irrotational fluid flows will be investigated in the context of scalar-tensor theories of gravity. In particular, the integrability conditions describing a consistent evolution of the linearised field equations of quasi-Newtonian universes are presented. We also derive the covariant density and velocity propagation equations of such models and analyse the corresponding solutions to these perturbation equations.DOI: 10.31526/LHEP.1.2018.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…where F and G depend on the kinematic, dynamical and gravito-electromagnetic quantities but not their derivatives [51,53,59]. It has been shown that the non-linear models are generally inconsistent if the silent constraint H ab = 0 is imposed, but that the linear models are consistent.…”
Section: Integrability Conditionsmentioning
confidence: 99%
“…where F and G depend on the kinematic, dynamical and gravito-electromagnetic quantities but not their derivatives [51,53,59]. It has been shown that the non-linear models are generally inconsistent if the silent constraint H ab = 0 is imposed, but that the linear models are consistent.…”
Section: Integrability Conditionsmentioning
confidence: 99%
“…The transformed linearised kinematics, dynamics and gravito-electromagnetic quantities from the quasi-Newtonian frame to the comoving frame are given as follows [51,53,59,60]:…”
Section: Integrability Conditionsmentioning
confidence: 99%